2012
DOI: 10.1029/2012pa002350
|View full text |Cite
|
Sign up to set email alerts
|

Early mid‐Holocene SST variability and surface‐ocean water balance in the southwest Pacific

Abstract: International audienceWe present early mid-Holocene records of Sr/Ca, δ18O and δ18Osw from marine archives collected in Vanuatu: two Porites sp. corals (6.7-6.5 ka BP) and a Tridacna maxima giant clam (6.2-6.0 ka BP). Sr/Ca, δ18O, and δ18Osw were used as proxies for sea surface temperature (SST) and sea surface salinity (SSS). The fossil geochemical records were compared to modern Porites sp. and T. maxima records. Reconstructed mean SSTs from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 94 publications
0
36
0
Order By: Relevance
“…Subsequently, the hydrological/thermal conditions in the tropical ocean reached the modern level, and the postglacial SST rise in the Southwest Pacific was completed (6.7e6.5 ka BP, Duprey et al, 2012). Observational and coral studies showed that decadal AM variability was tightly linked to the ENSO activity (Charles et al, 1997;Kumar et al, 1999;Yim et al, 2008), possibly via the midlatitude-tropical atmospheric teleconnection (Wang et al, 2000).…”
Section: Persistence Of Centennial-scale Am Changes In the Early Midhmentioning
confidence: 98%
“…Subsequently, the hydrological/thermal conditions in the tropical ocean reached the modern level, and the postglacial SST rise in the Southwest Pacific was completed (6.7e6.5 ka BP, Duprey et al, 2012). Observational and coral studies showed that decadal AM variability was tightly linked to the ENSO activity (Charles et al, 1997;Kumar et al, 1999;Yim et al, 2008), possibly via the midlatitude-tropical atmospheric teleconnection (Wang et al, 2000).…”
Section: Persistence Of Centennial-scale Am Changes In the Early Midhmentioning
confidence: 98%
“…In the western Pacific (Fig. 2a), the records show a significant decrease in ENSO variance during the early and mid-Holocene 16,17,30,37 ; there are only a few records from the 6-2 kyBP interval but these also show reduced ENSO variance. A decrease in ENSO variance is present throughout the past 7ky in the CP (Fig.…”
mentioning
confidence: 99%
“…We compare these data to an ensemble of nine state-of-the-art global climate models (GCMs) from the Paleoclimate Modeling Intercomparison Project (PMIP3 28 ), which include simulations of pre-industrial (piControl) as well as industrial era (historical) and MH (midHolocene) climate (Table S2). The datasets represent the most comprehensive collection of oxygen isotope measurements on Holocene corals 16,17,24,25,[29][30][31][32][33][34][35] and mollusks 26,[36][37][38] to date from the tropical Pa- Table S1 and Fig. S1).…”
mentioning
confidence: 99%
“…To acquire seasonal to monthly climatic information, most studies sample coral skeletons at very high-resolution intervals (ca. 1 mm or less; e.g., McCulloch et al 1994;Alibert and McCulloch 1997;Gagan et al 1998;McCulloch et al 1999;Sun et al 2004;Wei et al 2007;Deng et al 2009;Duprey et al 2012;DeLong et al 2013). However, high-resolution sampling requires a considerable number of subsamples for analysis, which makes coral-based climate reconstructions time consuming, labor intensive, and expensive.…”
Section: Introductionmentioning
confidence: 99%